2016
DOI: 10.1016/j.jde.2015.12.036
|View full text |Cite
|
Sign up to set email alerts
|

New blow-up phenomena for SU(n+ 1) Toda system

Abstract: Abstract. We consider the SU (n + 1) Toda system (S λ )

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…• In Theorem 1.3 it is essential to assume the matrix A to be positive definite. Otherwise, in [29,33,34,1] the authors build solutions to (1.3) whose masses can be arbitrarily large also on simply connected domains.…”
Section: Introductionmentioning
confidence: 99%
“…• In Theorem 1.3 it is essential to assume the matrix A to be positive definite. Otherwise, in [29,33,34,1] the authors build solutions to (1.3) whose masses can be arbitrarily large also on simply connected domains.…”
Section: Introductionmentioning
confidence: 99%
“…α 1 = α 2 = 2, Jost, Lin and Wang in [34] found that the local masses can only take 5 values. Moreover, all these blow-up values can occur as shown by Musso, Pistoia and Wei in [49] (see also Ao and Wang in [1]).…”
Section: Introductionmentioning
confidence: 77%
“…It is interesting to see whether any pair of the above is really the local masses of some sequence of blowup solutions of (1.2). For K = A 2 the existence of such a local solution has been obtained (see [30] and [24]). We remark that parts of Corollary 1.5 was already proved by Jost-Lin-Wang [15], and by the first author and the fourth author in [27].…”
Section: Definition 14 a Pair Of Local Massesmentioning
confidence: 93%